Liver Protection Effect of Red Rose Petal Methanol Extract in Copper-Induced Liver Injury in Male Wistar Rats - Hutagalung, Caroline Febrina; Girsang, Ermi; Mutia, Maya Sari; Suhartina, Suhartina; Natali, Oliviti (Biology, Medicine, & Natural Product Chemistry, 2023)
The human body requires low amounts of copper to maintain homeostasis, but high copper intake can cause various health problems. Many previous studies have been performed to look for natural products that can neutralize the excessive copper effect; one such natural product is a rose petal. Therefore, this study aims to investigate the liver protection effect of rose petals in copper-induced liver injury in male Wistar rats. This experimental study used thirty male Wistar rats that were grouped into five groups, including control, standard (quercetin), Rose Petal Methanol Extract-1 (400 mg/kg BW), 2 (800 mg/kg BW), and 3 (1,200 mg/kg BW). All groups were treated for 14 days, and all rats were given copper (II) sulfate suspension for the last three days. On the fifteenth day, all rats were sacrificed to obtain blood and liver tissue SGOT, SGPT, and liver histology study. The results showed that rose petal methanol extract significantly decreased SGOT and SGPT levels compared to the control group (P-value <0.05). The reduced area of ballooning degeneration and necrosis were in line with the increased dose of rose petal extract supported the liver protection effect of rose petal extract. Therefore, it can be concluded that rose petal methanol extract protects the liver against copper impacts.